IMPLEMENTATION OF GUIDED INQUIRY LEARNING MODEL TO TRAIN STUDENTS SCIENTIFIC LITERACY SKILLS IN CHEMICAL EQUILIBRIUM (Universitas Negeri Surabaya, 2020)
The research aims to describe the guided inquiry learning model implementation, students’ activities, students’ scientific literacy skills, and students’ responses to the implementation of guided inquiry learning in chemical equilibrium matter. This research used a Pre-Experimental Design with one group pretest-posttest design. The target in this research are 33 students XI grade at MAN Surabaya. The research result after the implementation of guided inquiry learning model shows that: 1) The average percentage of the learning implementation score in the meeting 1, 2, and 3 respectively 3,50; 3,67; and 3,77 with very good category, 2)Students have been using their times of 14,98%; 30,74%; and 24,69% to train scientific literacy skills include explain scientific phenomena, evaluating and designing scientific investigations, and interpret the data and scientific evidence, 3) Students’ scientific literacy skills have increased from pretest to posttest which proved by the total students who have gain score in the medium and high categories at 100%, 4) Students give positive responses to the implementation of a guided inquiry learning model to train students’ scientific literacy skills which the percentage of responses is 88,38% with very good category. This research states that the duration of student activity when implementing a guided inquiry learning model does not always result in better scientific literacy skills. Keywords: Guided Inquiry, Scientific Literacy, Chemical Equilibrium